Proceedings of International Conference on Muslim Society and Thought: Preface - Mahzumi, Fikri (Proceedings of International Conference on Muslim Society and Thought, 2019)
Let me brief you a little bit about the background of this conference. This conference is organized jointly by the Sunan Ampel State Islamic University in Surabaya and the Universiti Kebangsaan Malaysia. The idea behind this conference is our common interest in the need to understand better the nature, future and the fate of our Islamic communities in this very difficult time. We also are interested in developing new theories and critical views of our environment in which our religion of Islam is part of. This conference is therefore aimed at offering new understanding concerning our community and also of our religion vis-à-vis modernity. It also is aimed at challenging uncritical and unsympathetic views not only concerning Islam but also on other religions and religious communities at large. At the practical level, we gather here to build a commitment on the necessity of working together for the betterment of our Islamic community but also for humanity in general. Researchers and scientists should have a common view on how a better community can be achieved. Scientists like ourselves have a moral obligation to do something to build a better future. And what we can do toward that end is to share our views and expertise and see how that can be applied on the ground. In a nutshell, we gather here to build an intellectual platform on which our commitment to nourish the Islamic community can be carried out. A gathering such as this is a matter of urgency, considering that our community and religion –like any others- faces serious and demanding challenges. Whether we can survive these challenges or not very depends upon our ability to organize ourselves. Two things must be done to survive the challenges. First is to explore the potentials of the Islamic community in such a way as to make them ready to face those challenges. Our community cannot stay silent and passive in times of great difficulty such as this. Second, is to dig deep into the epistemological contents of our religion so as to provide a strong theoretical and metaphysical ground for our community to act accordingly. Hence the name of our conference is, International Conference on Muslim Society and Thought. We do hope that you enjoy your stay in Surabaya and the conference. We equally hope that you will benefit from the conference. It has been our pleasure to organize this conference and to host you all. So, be our guests. We thank you very much